Analisis Kelayakan Usaha Pengemasan Minyak Goreng Kelapa Sawit CV.Kaliserayoe Di Kecamatan Gunung Tanjung Kabupaten Tasikmalaya Jawa Barat - Herdiana, Elsa; Loho, Agnes Estephina; Pangemanan, Paulus Adrian (Sam Ratulangi University, 2023)
This study aims to analyze the feasibility of the palm cooking oil packaging business and to determine the large income from the palm cooking oil packaging business. The research was carried out for 5 months, starting from August to December 2020. The research location was at CV. Kaliserayoe, Tawangsari Village, RT 03 RW 03 Gunungtanjung Village, Gunungtanjung District, Tasikmalaya Regency, West Java Province. With a quantitative descriptive research method with data sources from primary data, namely cooking oil packaging business managers, and secondary data, namely from related agencies or institutions, the internet (google search and google schoolar) and libraries. The results showed that the income from the cooking oil packaging business carried out by CV. Kaliserayoe in one period (1 month) was IDR 32,053,188 and the cooking oil packaging business carried out by CV. Kaliserayoe was financially feasible, with an R/C value of 1.05.